INDIA UNVEILED: A GLOBAL DESTINATION OF SOCIAL COHESION AND RELIGIOUS DIVERSITY - Andrabi, Abroo Aman (ShodhKosh: Journal of Visual and Performing Arts, 2023)
India, a land of diversity and ancient cultural heritage, possesses a unique potential to attract global attention as a prominent tourist destination. It goes beyond mere tourism endeavors. It has the potential to drive economic growth, enhance international relations, foster interfaith understanding, and strengthen societal unity. By celebrating its diversity, India can emerge as a beacon of hope, inspiring the world toward a more interconnected and tolerant future. Moreover, emphasizing religious diversity can pave the way for greater interfaith understanding. As a melting pot of various religions, such as Hinduism, Islam, Christianity, Sikhism, and Buddhism, India has the potential to symbolize religious coexistence and mutual respect. This can have a far-reaching impact on promoting peaceful religious dialogue on a global scale. In this article, a few important aspects will be highlighted to emphasize India as a global destination of Social Cohesion and Religious Diversity. By highlighting these aspects, India can harness numerous benefits for its economy, international relations, and societal well-being.